Chemical composition and bioactivity of wild samples of Morchella esculenta from Portugal and Serbia. - Heleno, Sandrina A. (2013)
Mushrooms contain a huge diversity of biomolecules with nutritional1 and/or bioactive properties.2 , 3 Morchella esculenta (L.) Pers. (morel) is one of the most widely appreciated wild edible mushrooms. Herein, a comparative study on chemical composition (nutritional value, primary and secondary metabolites), antioxidant properties (scavenging activity, reducing power and inhibiPEsttion of lipid peroxidation), and antimicrobial activity (antibacterial and demelanizing properties) of two samples of Mo r c h e l l a es c u l e n t a (morel) from different countries (Por tugal and Serbia) was performed. This species was chosen for being one of the most highly prized edible mushrooms in the world. Both samples are rich in carbohydrates (including free sugars) and proteins, and c o n t a i n seve r a l bi o - act ive compounds such as organic acids, phenolic compounds and tocopherols. Polyunsaturated fatty acids were the most abundant compounds followed by mono or saturated fatty acids. Sample from Portugal (SP) gave higher radical scavenging activity and reducing power, while sample from Serbia (SS) showed higher lipid peroxidation inhibition. Both samples gave antibacterial acti-vity against five b a c t e r ia (in some cases even bet ter than standard ant ibiot ics) and demelanizing activity against four micromycetes, showing SS higher activities. As far as we know, this is the first study reporting chemical compounds and bioactivity of morel samples from Por tu g a l an d Ser b i a . Furthermore, a novel method f o r ev a l u a t i o n of demelanizing activity was presented.